The Influence of Fear and Predator-Dependent Refuge on The Dynamics of A Harvested Prey-Predator Model with Disease in Predator - Abdullah, Hussein Sabah; Bahlool, Dahlia Khaled (Iraqi Journal of Science, 2025)
This paper discussed fear and predator-dependent refuges in a harvested prey-predator model with disease in predator with using the relationship between a predator's consumption of prey and the presence of fear in the prey in the existence of an infected predator in the environment. The solution was consistently limited in order to assure the availability of a solution due to the availability of conditions. The solution points for the system were also found, and the conditions for the approach of estimating the solution has been studied stability. We studied the bifurcation of the system and illustrate that it works. This research examined the effect of harvest factor on prey impact, as well as the combined influence of death in the unwell predator and the harvest of its available resources. It makes a major effect on the outcome of the system. The outcomes obtained by varying the parameters are displayed in numerical work. And theoretical solution was confirmed using Mathematica graphing.